ANALISIS SUPPLY CHAIN MANAGEMENT TERHADAP KEUNGGULAN BERSAING PADA KOPERASI PRODUKSI PANGAN DI KABUPATEN BANDUNG BARAT - Yun Yun; Asep Kurniawan (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Food Production Cooperatives can be utilized by the government to maintain the balance ofdomestic food supply, although currently food Production cooperatives do not have a high contributionto the Indonesian economy. Problems arising from food production cooperatives are low innovation andproduct development that makes the competitiveness of food production cooperatives relatively low.The purpose of this study to determine the effect of supply chain management on the competitiveadvantage of food cooperatives in West Bandung District.The research method used is descriptivequantitative analysis. Quantitative analysis method used path analysis. The sample in this research isthe leadership of Food Production Cooperative in West Bandung District. The measurement of supplychain managment uses dimension of strategic supplier partnership, customer relationship andinformation sharing. The results of this study indicate the partial and simultaneous influence of strategicsupplier partnership, customer relationship and information sharing on competitive advantage.